Better safe than sorry: Evaluating the implementation process of a home-visitation intervention aimed at preventing unintentional childhood injuries in the hospital setting - Shalev, Ligat; Rudolf, Mary C. J.; Spitzer, Sivan (Frontiers in Health Services, 2022)
Background: Child home injuries prevention interventions have rarely been implemented in hospitals. The SHABI program ('Keeping our Children Safe'; in Hebrew: 'SHomrim Al BetIchut Yeladenu') recruits at-risk families arriving with child injury to the Emergency Department. Medical/nursing students conduct two home visits four months apart, providing safety equipment and guidance. One hundred thirty-five families had a first visit and 98 completed the second. 50% of families were ultra-Orthodox Jews, 11% Arab, and 28% had ≥3 preschool children. We investigated SHABI’s implementation using the Consolidated Framework for Implementation Research (CFIR). Methods: Between May 2018-March 2021 SHABI was implemented in the Emergency Department of a hospital in Israel's northern periphery, an area with high child injury rates. The Implementation process was examined through Emergency Department medical records and tracking registries, hospital management, nurses', and home visitors' meetings notes (n=9), and a research diary. Hospital's inner setting and SHABI's characteristics were evaluated through interviews with hospital management, nurses, and home visitors 8 months after baseline (n=18). Home visitors’ characteristics were evaluated through interviews, post-visit questionnaire on challenges encountered (n=233), families' perceptions of SHABI and home visitors' skills through telephone interviews (n=212); and home visitors awareness of dangers at home (n=8) baseline and 8 months later. Qualitative data were analyzed through explanatory content analysis according to CFIR constructs. Quantitative data were analyzed using X2 and Wilcoxon test for dependent subgroups. Results: Despite alignment between SHABI and the hospital’s mission, structural hospital-community disconnect prevented implementation as planned, requiring adaptation and collaboration with the medical school to overcome this barrier. Recruitment was included in the initial patient triage process but was only partially successful. Medical/nursing students were recruited as home visitors, and following training proved competent. Children were a distraction during the visits, but home visitors developed strategies to overcome this. Conclusions: Injury prevention programs in hospitals have significant benefits. Identifying implementation barriers and facilitators allowed implementers to make adaptations and cope with the innovative implementation setting. Models of cooperation between hospital, community and other clinical settings should be further examined.